Iodine Concentration Effects on Linear Growth of Children after Nutrition Behavior intervention, Central Highland of Ethiopia: A Cluster Randomized Community Trial - Ferede, Abebe; Belachew, Tefera; Abera, Muluemebet (International Journal of Child Health and Nutrition, 2022)
Background: To improve the iodine status and growth of children was not documented in Ethiopia. This study aimed to determine the effects of nutrition behavior communication change (BCC) on improving iodine status and growth of children 6 to 59 months. Methods: A community cluster randomized trial with a single treatment arm was conducted from February 2018 to April 2020. “Kebeles” [lower administrative units] were randomly assigned to either the intervention or the control cluster. Mothers and their paired children were randomly selected from kebeles. Anthropometry data and urine samples were collected at baseline and end-line surveys. Percentile rank and Independent t-test were used to determine the difference between arms. Finally, Generalized Estimating Equation (GEE) is used to isolate independent predictors. Results: At baseline, 97.83 % (n = 812) mothers/ caregivers and paired children were enrolled for the trial study, but at the end-line, 88.05% (n =715) of children completed the intervention. Iodine deficiency prevalence was higher (11.82%, n = 96) at baseline and reduced to 6.15 % (n =44) at the end-line. The growth defect among children was 41 %( n = 332) at the baseline and declined to 28.67 %( n=205) at the end-line, while among interventions reduced by more than two times (39% to 12.81%). At the baseline, the median UIC among the intervention group was 106.0µg/L and increased to 207.190µg/L. The prevalence of iodine deficiency among intervention was 14.29% (n = 58) at the baseline and lowered to 3.45% (n=14) at the end-line, but a slight increment observed among control from 9.36% to 9.71% at end-line. The end-line median UIC was very high (210.56µg/L ± 150 compared to the baseline median UIC (107µg/L ± 8.66). Most (43.6%) of the intervention group found in the 4th and 5th percentile ranks factions of UIC by Height (Ht) mean differences. Being an intervention group increased Ht by 10.85cm (β =10.85, Std. E = 0.33). Likewise, for 1µg/l UIC change a 1cm (β = 1.0, p = <0.05) Ht change predicted at the end-line. Conclusions: Findings from this trial enhance nutrition behavior communication to improve the iodine status and growth of young children in the community. Longitudinal studies are needed to determine the level of iodine deficiency disorders in the community.